Исповедь на краю: роман / Е. Михайлова - Михайлова Евгения (Детектив-событие, 2012)
Экземпляры: (20220419) / Инвентарный номер: 36104 / Цена: 61.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 69 / ГРНТИ: 17 / ББК: 84(2=411.2)6